2019
DOI: 10.2355/isijinternational.isijint-2018-677
|View full text |Cite
|
Sign up to set email alerts
|

Non-Isothermal Melt Crystallization Kinetics for CaO–Al<sub>2</sub>O<sub>3</sub>–B<sub>2</sub>O<sub>3</sub> F-Free Mould Fluxes

Abstract: Efforts have been made to develop fluorine-free mould fluxes for the continuous casting of steel process. In this work the crystallization behaviour of fluorine-free mould slags based on the CaO-Al 2 O 3-B 2 O 3 system was investigated by differential scanning calorimeter (DSC) and scanning electron microscopy equipped with energy dispersive spectroscopy(SEM-EDS). The crystallization kinetics for Ca 3 Al 2 O 6 primary crystals was analysed by combining modified Avrami analysis with Friedman isoconversional met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…That is to say, the crystallization of Ca 2 SiO 4 during cooling follows anti-Arrhenius behavior, which was found in crystallization of polymers, 20) traditional mold fluxes, 23) and F-free mold fluxes. 13) For Sample 1, the one with the highest Na 2 O content, E α takes greater negative values at lower values of relative crystallinity, corresponding to temperatures closer to liquidus. The E α increases as the extent of conversion rises and the temperature decreases.…”
Section: Effective Activation Energy For Crystallization Of Ca 2 Siomentioning
confidence: 92%
See 1 more Smart Citation
“…That is to say, the crystallization of Ca 2 SiO 4 during cooling follows anti-Arrhenius behavior, which was found in crystallization of polymers, 20) traditional mold fluxes, 23) and F-free mold fluxes. 13) For Sample 1, the one with the highest Na 2 O content, E α takes greater negative values at lower values of relative crystallinity, corresponding to temperatures closer to liquidus. The E α increases as the extent of conversion rises and the temperature decreases.…”
Section: Effective Activation Energy For Crystallization Of Ca 2 Siomentioning
confidence: 92%
“…In a previous laboratory work, 13) non-isothermal melt crystallization kinetics for CaO-Al 2 O 3 -B 2 O 3 F-free mold fluxes, for continuous casting of high aluminum steels, through modified Avrami analysis and Friedman differential isoconversional method, was studied. Crystallization mechanisms and effective activation energy of crystallization were determined for different compositions, for the first crystal, which precipitates from melt (Ca 3 Al 2 O 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The thermodynamic liquidus temperature for slag cannot be calculated from thermodynamic package due to the limiting thermodynamic data for this new slag system. But according to our previous study on crystallization of the same slag, 42) the slag with the lowest CaO/Al 2 O 3 ratio (CaO/Al 2 O 3 = 0.9) has the fastest crystallization, which could also contribute to the highest breaking temperature. Correlation between structural information and physiochemical properties of slags could be explored.…”
Section: Effects Of the Cao/al 2 O 3 Mass Ratio On Viscositymentioning
confidence: 94%
“…Shu et al [83] also studied the non-isothermal crystal- the Avrami parameter n was found to be close to three, indicating instantaneous bulk nucleation and 3D crystal growth. Furthermore, using the Friedman isoconversion method, [76] they calculated the effective activation energies for crystallization of Ca 3 Al 2 O 6 in all the mold fluxes studied and reported negative values of activation energy, which agreed well with the observations of Seo et al [78] in earlier investigation with conventional CaO-SiO 2 -CaF 2 -based mold fluxes.…”
Section: Studies On Non-isothermal Crystallization Kinetics Of Mold Fluxes Using Thermoanalytical Techniquesmentioning
confidence: 97%
“…Watanabe et al [81] studied the effects of alkali oxide addition on the kinetics of crystallization in CaO-SiO 2 -CaF 2 -based mold fluxes using DTA and reported that alkali oxides such as Li 2 O, K 2 O, and Na 2 O enhanced cuspidine crystallization. Choi et al [82] and Shu et al [83,84] examined the non-isothermal crystallization behavior of F-free mold fluxes using thermoanalytical methods. While Choi et al [82] used the Matushita and Sakka [63][64][65][66][67] equation, Shu et al [83,84] used the Friedman method [76] and therefore the numerical accuracy of the results reported by Shu et al [83,84] may be higher for reasons already discussed.…”
Section: Studies On Non-isothermal Crystallization Kinetics Of Mold Fluxes Using Thermoanalytical Techniquesmentioning
confidence: 99%